THE INFLUENCE OF PROMOTIONS AND FLASH SALE ON THE DECISION TO USE THE SHOPEE APPLICATION IN MATARAM CITY - Dwi Yanti, Yuni; Permadi, Lalu Adi; Retnowati, Weni (Jurnal Magister Manajemen, 2024)
The aim of this research is to determine the significance of the influence of promotions and flash sales on decisions to use the Shopee application. The population of this research is Mataram city residents who have shopped on the Shopee application at least 1-3 times. The type of research used is quantitative research with a causal associative approach. Data collection techniques and tools use questionnaires distributed online. This research was located in Mataram City and the research population used a sample of 100 respondents. Using non-probability and purposive sampling techniques. The research results show that promotion has a positive and significant effect on the decision to use the Shopee application in the city of Mataram. Flash sales have a positive and significant effect on the decision to use the Shopee application in the city of Mataram.   The aim of this research is to determine the significance of the influence of promotions and flash sales on decisions to use the Shopee application. The population of this research is Mataram city residents who have shopped on the Shopee application at least 1-3 times. The type of research used is quantitative research with a causal associative approach. Data collection techniques and tools use questionnaires distributed online. This research was located in Mataram City and the research population used a sample of 100 respondents. Using non-probability and purposive sampling techniques. The research results show that promotion has a positive and significant effect on the decision to use the Shopee application in the city of Mataram. Flash sales have a positive and significant effect on the decision to use the Shopee application in the city of Mataram.